The development of prospective memory across adolescence: an event-related potential analysis - Bowman, Candice; Cutmore, Tim; Shum, David (Frontiers in Human Neuroscience, 2015)
Prospective memory (PM) is an important cognitive function vital for day-to-day functioning. Although there has been extensive research into the decline of PM in older adulthood, little is known about its developmental trajectory throughout adolescence, a time of important brain maturation. In the present study, the development of PM was examined in 85 participants across the following groups: 12 to 13-year-olds (n = 19), 14 to 15-year-olds (n = 21), 16 to 17-year-olds (n = 19), and 18 to 19-year-olds (n = 26). A 30-cue (30 minute) event-based PM task (with font-colour stimuli as PM cues and a lexical-decision task as the ongoing task) was used while recording Event-Related Potentials (ERPs). The well-established neural correlates of PM, the N300 and parietal positivity, were examined across the age groups. In addition, hierarchical multiple regressions were used to examine the unique contribution of executive functioning measures (viz., the Self-Ordered Pointing Task [SOPT], the Stroop task, and Trail Making Test [TMT]) on the ERP components of PM (after controlling for age). First, the established components of ERPs associated with prospective remembering (i.e., N300 and parietal positivity) were detected for each age group. Second, although there were no significant age- group differences on the amplitude of the N300, the amplitude of the parietal positivity was found to be different between the 12 to 13-year-olds and 18 to 19-year-olds (viz., the 12 to 13-year-olds had the highest amplitude). Third, for the contribution of executive functioning measures on the amplitude of the ERP components of PM, the regression on the N300 was not significant, however, the SOPT beta weights were significant predictors of the amplitude of the parietal positivity. This relationship was found to be specific for the central and right electrode region. These findings are discussed within the context of brain development and executive functioning along with particular task demands